Geochemical characteristics, origin and forms of sulphur distribution in the Talcher coalfield, India. (15th May 2022) - Gopinathan, P.; Jha, Madhu; Singh, Ashok K.; Mahato, Abhishek; Subramani, T.; Singh, Pradeep K.; Singh, Vivek
Highlights: Geochemical characteristics, origin and forms sulphur distribution with reference to Talcher coalfield. The total sulphur concentration ranges from 0.5% to 1.13%, which falls under category of low-sulphur coals. Organic sulphur accounts for 70%, pyritic sulphur accounts for 25% and sulphate sulphur ≤5%. FESEM technique expose that the sulphide minerals presents pyrite (FeS2 ), marcasite (FeS2 ) and Sphalerite (ZnS). Petrographic study reveal that macerals account for 69%, pyrite 1.8% and mineral matter 29.28% of the total mass of coal. Abstract: Geochemical studies conducted on samples from the Talcher coal field can help elucidate the occurrence, origin and different forms of Sulphur in the area. In this coalfield, sulphur is present as organic sulphur, pyritic sulphur, and sulphate sulphur. The total sulphur concentration ranges from 0.5% to 1.13%, which falls under category of low-sulphur coals. Organic sulphur accounts for 70%, and pyritic sulphur accounts for 25% of the total sulphur in the Talcher coal. The presence of a minor proportion of sulphate sulphur (approximately ≤ 5%) indicates that Talcher coals are formed under non-marine environmental conditions. Results from proximate analysis expose the gross composition of coal. The air dried results indicate that, the moisture content varies from 2.6 to 4.8%, ash content ranges from 29.7 to 45.6%, volatile matter ranges from 24.54 to 29.65%, and fixed carbon content varies from 25.96 to 37.25%. It is observed that when the ash percentage of coal samples is less than 40%, the gross calorific value of the Talcher coalfield ranges from 4000 to 5000 kcal/kg, and when the ash percentage of the coal samples is greater than 40%, the gross calorific value is less than 3000 kcal/kg. The elemental compositions of the Talcher coalfield were also determined based on the dry mineral matter free basis. Carbon, hydrogen, nitrogen, sulphur, and oxygen content were determined. Macerals and mineral matter were studied using a coal Petrological microscope. It was observed that macerals account for 69% of the total mass of coal while pyrite represent 1.8% and other minerals 29.28%. Results obtained using the field emission scanning electron microscope technique show that the major sulphide minerals present in the Talcher coals are pyrite (FeS2 ) and marcasite (FeS2 ), with pyrite being the more common. Sphalerite (ZnS) was found in some samples. The study has revealed the geochemical characteristics, origin and forms of sulphur distribution in the Talcher coalfield.